Circulation of Type 2 Vaccine-Derived Poliovirus in China in 2018–2019 - Zhao, Hehe; Ma, Xiaozhen; Tang, Haishu; Zhang, Yong; Chen, Na; Kaisaier, Wusiman; Wang, Qi; Wang, Cheng; Zhu, Shuangli; Qi, Qi; Liu, Yu; Ma, Qianli; et al. (Open forum infectious diseases, 2021)
Abstract Background China implemented the globally synchronized switch from trivalent oral poliovirus vaccine (tOPV) to bivalent OPV (bOPV) on May 1, 2016. During April 2018 to May 2019, the first outbreak caused by type 2 circulating vaccine-derived poliovirus (cVDPV2) after the switch occurred in Xinjiang and Sichuan, China. Methods. We performed sequence analysis of VP1 and the whole genome to determine the genomic characteristics of type 2 cVDPVs, and carried out coverage surveys to assess the risk of viral propagation. Surveillance for environment and acute flaccid paralysis was intensified to enhance case ascertainment. Results. Comparison of the complete genomes between early (Xinjiang strain) and late strains (Sichuan strains) revealed that recombination pattern and reverse mutation of attenuation sites had been fixed early, but the mutations of the neutralizing antigenic sites were introduced over the circulation. The Markov Chain Monte Carlo tree showed that the cVDPV2 initial infection was April 2016, earlier than the switch. So, we speculated that the cVDPV2 was originated from tOPV recipients and spread among children with a low level of immunity against the type 2. Conclusions The detection of this outbreak combined acute flaccid paralysis (AFP) surveillance with environmental surveillance (ES) indicates that ES should be expanded geographically to further complement AFP surveillance.